2021
DOI: 10.2991/absr.k.210621.028
|View full text |Cite
|
Sign up to set email alerts
|

The Type and Distribution of Violin Crab (Uca) at Mangrove Forest of Kahyapu, Enggano Island and The Gulf of Muaro, Labu Nawi, Bengkulu City

Abstract: Violin Crab (Uca) is type of crab living in mangrove habitat as a detrivore. In Bengkulu, the mangrove forest zone locates in many areas, including Kahyapu, Enggano Island and Gulf of Muaro Labu Nawi, Pulau Baai, Bengkulu City. The objective of this experiment was to investigate the pattern of Violin Crab distribution at mangrove forest in Kahyapu and Gulf of Muaro. The methodology used in this experiment, carried out from 2017 to 2018, was a survey done by random sampling. The samples were taken from 2 statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The abundance of species in a community will affect the diversity of ecosystems in the area. The variety of a species will decrease if the number of species and there are variations in the number of individuals of a larger species (Sawitri et al 2019;Duya et al 2021). Diversity (H') in the mangrove ecosystem, especially for the life of saving crabs or burrowing crabs, can be influenced by various factors such as the growth of mangrove vegetation, tides, sound pollution, and vibrations caused by human and natural activities (Sinamo et al 2020;Hasan and Padjadjaran 2021).…”
Section: Biodiversity Of Ocypodidae and Sesarmidae Crabsmentioning
confidence: 99%
“…The abundance of species in a community will affect the diversity of ecosystems in the area. The variety of a species will decrease if the number of species and there are variations in the number of individuals of a larger species (Sawitri et al 2019;Duya et al 2021). Diversity (H') in the mangrove ecosystem, especially for the life of saving crabs or burrowing crabs, can be influenced by various factors such as the growth of mangrove vegetation, tides, sound pollution, and vibrations caused by human and natural activities (Sinamo et al 2020;Hasan and Padjadjaran 2021).…”
Section: Biodiversity Of Ocypodidae and Sesarmidae Crabsmentioning
confidence: 99%
“…Several researchers also reported that groups of crabs from the genus Uca quite dominate the mangrove ecosystem in Bali, including on the Pejarakan Buleleng coast (Ginantra et al 2021), in the mangrove forest of Merta Sari Sanur (Indraswari et al 2018), the mangrove forest of Kampoeng Kepiting Tuban Badung Bali (Krisnawati et al 2018) and in the Benoa Badung mangrove forest (Wahyudi et al 2014). Crabs from the genus Uca are also a common genus in mangrove ecosystems in several mangrove forests in Indonesia, including in the Monta Bima mangroves, mangrove forest of Kahyapu, Enggano Island (Duya et al 2021), in the Probolinggo mangrove forests, East Java (Riswandi et al 2019), in Tanjung Panjang Mangrove Forest, Gorontalo Sulawesi (Katili et al 2017;Lapolo et al 2018).…”
Section: Crustacean Diversitymentioning
confidence: 99%